Reliability of Insulation Systems and Its Impact on Electric Machine Design for Automotive and Aviation Applications - Arsham Asgari; Lucas Vincent Hanisch; Johanna Anspach; Jonas Franzki; Maik Kahn; Michael Kurrat; Markus Henke (Energies)
The growing use of electric machines in safety-critical applications, such as electromobility and electrified aviation, underscores the importance of ensuring their reliability. The reliability of electric machines will increasingly depend on the electrical insulation system (EIS), as they face higher voltage levels, faster switching semiconductors, and more demanding environmental conditions. The influence that the dimensioning of the enameled copper wire and the slot insulation material has on the reliability of the EIS and how different impregnation resins and novel high-thermal-conductivity (HTC) configurations of the slot insulation materials affect it will be demonstrated. This is because in addition to increased reliability, the performance of electrical machines is to be improved at the same time. A case study for an aviation application is used to show how the EIS influences the machine design. Depending on the EIS, the copper and iron losses and the conductor temperature have been investigated with the aim of keeping them as low as possible while simultaneously minimizing the risk of PD.